Malnutrition: Modulator of Immune Responses in Tuberculosis - Chandrasekaran, Padmapriyadarsini; Saravanan, Natarajan; Bethunaickan, Ramalingam; Tripathy, Srikanth (Frontiers in Immunology, 2017)
Nutrition plays a major role in the management of both acute and chronic diseases, in terms of body’s response to the pathogenic organism. An array of nutrients like macro- and micro nutrients, vitamins etc are associated with boosting the host's immune responses against intracellular pathogens including mycobacterium tuberculosis (M.tb). These nutrients have an immunomodulatory effects in controlling the infection and inflammation process and nutritional deficiency of any form, i.e., malnutrition, may lead to Nutritionally Acquired Immunodeficiency Syndrome, which greatly increases an individual’s susceptibility to progression of infection to disease. This narrative review looks at the various mechanisms by which nutrition or its deficiency leads to impaired cell mediated and humoral immune responses which in turn affects the ability of an individual to fight Mycobacterium tuberculosis infection or disease. There is very little evidence in the literature that any specific food on its own or a specific quantity can alter the course of TB disease or be effective in the treatment of malnutrition. Further clinical trials or studies will be needed to recommend and to better understand the link between malnutrition, tuberculosis and impaired immunity.